Dinamiche evolutive delle imprese familiari: Il ruolo del capitale umano e del capitale sociale nel ricambio generazionale - Masciarelli, Francesca; Principe, Andrea (Piccola Impresa / Small Business, 2010)
This paper aims to shed new light on the effects of social capital and human capital on family firms’ succession. Drawing on theory on family firms, we identify three succession models: conservative, wavering and proactive. Empirically, we adopt a multiple case study approach involving a theoretical sample of six family firms. From our research, we conclude that the successor’s level of social capital and human capital contributes in defining the succession model adopted by the firm. This study contributes to bridge literature on family firm with social capital and human capital theories and provides some insights for managers and entrepreneurs that are approaching the succession process.